ANALISIS PERTUMBUHAN EKONOMI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI ( KABUPATEN/KOTA DI PROVINSI JAWA TENGAH - Wicaksono Pambudi, Eko; Miyasto, Miyasto (Diponegoro Journal of Economics, 2013)
Economic growth has an important role in decreasing poverty and creating jobs. The aim of this research was to analize factors that influence economic growth. This research had been done in the regency/municipalityâ€™s economic growth in Central Java Province during five years period 2006-2010. The model applied in this research is based on the neo classic growth theory proposed by Solow, capital and labour factors. Using combination data between the number of cross section data (35 regencies/cities) and the number of time series data during 5 years (2006-2010), this research used panel data with 175 observation method.Â The result of this research indicated that aglomeration have negative effect but insignificant toward the economic growth, invesment have positive effect and significant to influence the economic growth, working work-force variabel have positive and significant influence to the economic growth, and human capital variabel have positive but insignificant toward the economic growth.